2005
DOI: 10.1159/000085671
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the pattern of X-linked gene expression between fetal bovine muscle and fibroblast cultures derived from the same muscle biopsies

Abstract: The sex determination system in mammals creates an imbalance between males and females in the number of X chromosomes. This imbalance is compensated through transcriptional silencing of one of the two X chromosomes in female diploid cells by epigenetic modifications. Although common for mammals, X inactivation shows marked species-specific differences in mechanisms and end results, and provides a unique opportunity to study epigenetic regulation of gene expression. The aim of the present study was to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 136 publications
0
7
0
Order By: Relevance
“…Previous studies from this laboratory had shown that the expression status of genes on the bovine X chromosome is more similar to that of the human X than the murine X and that the levels of expression of many of these genes are highly variable and under epigenetic control [Nino-Soto et al, 2005. Since histone modifications and histone variants are intimately involved in epigenetic regulation of gene expression we undertook a study to examine the spatial relationship of different histone variants on the bovine X chromosome using an immunostaining approach (with 4 different antibodies) in the context of DNA replication, heterochromatinization and gene silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from this laboratory had shown that the expression status of genes on the bovine X chromosome is more similar to that of the human X than the murine X and that the levels of expression of many of these genes are highly variable and under epigenetic control [Nino-Soto et al, 2005. Since histone modifications and histone variants are intimately involved in epigenetic regulation of gene expression we undertook a study to examine the spatial relationship of different histone variants on the bovine X chromosome using an immunostaining approach (with 4 different antibodies) in the context of DNA replication, heterochromatinization and gene silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Histone 2A (H2A) was chosen as autosomal control based on previous reports (Robert et al, 2002;Lonergan et al, 2003a). Design of specific PCR primers and quantification of transcripts using quantitative realtime PCR was performed as previously described (Nino-Soto et al, 2005). Briefly, PCR products for each gene tested were used to build specific standard curves to perform absolute quantification (Bustin, 2000) in a Light Cycler instrument with the Light Cycler FastStart DNA Master Mix SYBR Green I kit.…”
Section: Rna Extraction and Cdna Synthesismentioning
confidence: 99%
“…However, as has been reported, UBE1 displays significant differences in gene expression depending on whether it is analyzed in native tissue or in cell cultures derived from the same biopsies. 13 Therefore, we performed real-time PCR in white blood cells of the still living index patient of family #15. PCR amplification and detection was performed on a Sequence Detection System (ABI PRISM 7000, Applied Biosystems) applying the standard two-step protocol (45 cycles, annealing temperature 61 C) recommended by ABI.…”
mentioning
confidence: 99%